(3cJGH ajg Yed GdSGYGJ GdJj JQej HGdHfGObs - (3ajdhf GdEScfOQj GdMcjes
(3ChdgG (B:s
(3HYO GdHSedI bGd ajdhf gPG GYed SGYGJ GdeGA GdJj JQej HGdHfGOb hajgG VQhH ef GdMQcGJ s
(3BNQgG (B:s
(3dC, GdJbOjQ gh edGc GdYed hUMJg dFdG jdJa HYVgeG HHYV hEf TFJ C, Jchf GdNRGfI eOhQI Ch THjI HGdWjdSGf hgcPG QCjJgG s
(3Vef eLehY , JQJjHgG (B: 3s
(3hjJdhg aGFOIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3ef GgOGAGJ O (B/ (3SRcjf ddeYgO s
Keywords: (3eJaQbGJs